Front Cover: Gold Nanostars: Synthesis, Optical and SERS Analytical Properties (Anal. Sens. 3/2022). Issue 3 (26th April 2022) - Becerril‐Castro, I. Brian; Calderon, Irene; Pazos‐Perez, Nicolas; Guerrini, Luca; Schulz, Florian; Feliu, Neus; Chakraborty, Indranath; Giannini, Vincenzo; Parak, Wolfgang J.; Alvarez‐Puebla, Ramon A.
Abstract : The cover picture shows a crowd scene that symbolizes the capability of the gold nanostars to optically detect and classify, through SERS, events in very complex samples as required, for example, in liquid biopsies where the tumoral circulating cells hide in the pool of normal cells. More information can be found in the Review by V. Giannini, W. J. Parak, R. A. Alvarez‐Puebla and co‐workers .